Peran Kepercayaan Memediasi Pengaruh Kemudahan dan Keamanan Terhadap Keputusan Penggunaan QRIS di Kalangan UMKM Kota Denpasar - Martini, Ida Ayu Oka; Jaya, I Ketut Wira Dharma (Economic Reviews Journal, 2025)
This phenomenon indicates that QRIS adoption among MSMEs in Denpasar City is not yet fully equitable. The persistence of business actors who have not actively used QRIS illustrates the gap between the availability of technology and the ability of MSMEs to utilize it optimally. The decision to use a digital payment system is influenced by various variables, including convenience and security. Trust plays a crucial role in bridging the relationship between convenience and security on the decision to use QRIS. High trust makes MSMEs feel confident that QRIS services are reliable, thus encouraging them to continue using it. Conversely, when trust decreases, either due to security factors or suboptimal convenience, the decision will be affected. This study used a purposive sampling method with 105 selected respondents. Data collection was conducted through a 5-point Likert scale questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed that convenience significantly influences the decision to use. Convenience significantly influences trust. Security significantly influences the decision to use. Security significantly influences trust. Trust significantly influences the decision to use. Convenience does not significantly influence the decision to use through trust. Security does not significantly influence usage decisions through trust.